Environments of the climatic optimum of MIS 11 in Britain: evidence from the tufa sequence at Hitchin, southeast England. (25th March 2021) - Sherriff, J. E.; Schreve, D. C.; Candy, I.; Palmer, A. P.; White, T. S.
ABSTRACT: Marine Oxygen Isotope Stage 11 (MIS 11, Hoxnian Interglacial) is an important interval for understanding both climate change in an interglacial partially analogous to the Holocene and the response of geomorphic processes, biotic systems, and hominin populations to these changes. In Britain, many sites correlated to MIS 11 have not been studied since the mid‐20th century and require reinvestigation, including the Hitchin tufa sequence, where a rich, non‐marine molluscan assemblage was originally recovered. Re‐excavation of the Hitchin tufa sequence for this study was focussed on combined sedimentological, micromorphological and geochemical analyses of the deposits. These indicate that tufa formation occurred within a perched springline system under temperate climatic conditions. Shifts between paludal and fluvial tufa facies within this system occur concomitantly with changes in carbonate geochemistry, representing increased humidity caused by a change in rainfall amount or seasonality. This research enables a correlation of the sequence to the climatic optimum of MIS 11c, the main warm phase of MIS 11, and permits further insights into temperature and hydrological changes in this interval by generating the first geochemical records of hydroclimatic evolution during the MIS 11 thermal maximum in Britain.